(untitled) (Fiep Bulletin - online, 2011)
Today, obesity is a pathology that affects several countries, being considered a risk for the health. Young Down Syndrome (DS) patients have higher probability of becoming obese compared to the general population, due to cognitive and physical characteristics, therefore, physical activity programs for this population should be developed and tested to enable a higher daily caloric expense. The objective of this study is to analyze the effects of a swimming program, with and without fins, in the learning of the stroke crawl and body composition of young Down Syndrome patients. The group evaluated was formed by 7 young DS patients, with ages between 15 and 32 years, submitted to a swimming class program during three months, with 3 times weekly frequency, with duration of 50 minutes each and divided in 5 sets of 10 minutes, with the following exercises: fluctuation, breath, rhythm, balance and displacement. Pollock protocol (1985) was used to evaluate the body composition. Langendorfer and Bruya (1995)´s table of aquatic readiness was used for the analysis of the motor learning. Faced with the variables studied, improvements in the motor learning have been found, however, no evolution has been found in body composition with the program proposed.